Surfactant therapy in late preterm infants: respiratory distress syndrome and beyond - Sürmeli-Onay, Özge; Korkmaz, Ayşe; Yiğit, Şule; Yurdakök, Murat (The Turkish Journal of Pediatrics, 2012)
A significant ratio of late preterm infants receives surfactant therapy (ST) for respiratory distress syndrome (RDS) and for other neonatal lung diseases characterized by surfactant inactivation or dysfunction. We aimed to investigate the clinical and therapeutic characteristics and outcomes of late preterm infants who received ST in the last 10 years in our neonatal intensive care unit. During the 10-year period, 77 late preterm infants received ST. The underlying lung diseases were RDS in 51 (66.2%), congenital pneumonia in 15 (19.5%), congenital diaphragmatic hernia in 4 (5.2%), pulmonary edema due to hydrops fetalis in 4 (5.2%), and acute respiratory distress syndrome (ARDS) in 3 (3.9%) infants. Pulmonary hypertension was a significant predictive factor for mortality. Although RDS was the main cause of respiratory failure in late preterm infants, other lung diseases leading to surfactant dysfunction were not rare; therefore, ST should be considered as a life-saving treatment.